THE ROLE OF FRENCH LOANWORDS WITHIN THE ENGLISH LEXICON PERTAINING TO FASHION AND CLOTHING (Journal of Universal Science Research, 2025)
The English language boasts a rich and diverse history, significantly shaped by the influx of words borrowed from other languages.  "The Role of French Loanwords within the English Lexicon Pertaining to Fashion and Clothing" is underscored by the significant influence of French culture and language on the English lexicon, particularly in the realm of fashion and clothing. As global fashion trends continue to evolve and intermingle, understanding the origins and implications of these loanwords becomes increasingly relevant. French has historically been associated with elegance, sophistication, and style, making its vocabulary particularly prominent in discussions about fashion. The integration of French terms into English reflects not only linguistic adaptation but also cultural exchange and the evolution of fashion as a form of expression. On this line French borrowings stand out with their quantity and usage in the language. Specially fashion related French borrowings were integral to the fabric of English clothing related terms and still continue to shape its dynamic nature.